Crecimiento comparativo de las especies de robalo del pacifico costarricense cultivado en jaulas. - Günther, Jorge (1998)
Several species of Pacific snooks of Costa Rica, obtained as 50 mg larvae in Punta Morales, Gulf of Nicoya, were grown together in a cage suspended in the water supply channel of a shrimp farm for 222 days. Only the species Centropomus nigrescens, viridis, robalito and unionensis could be identified at the end of the experiment. Within the groups nigrescens/viridis and unionensis/robalito no differences in growth rate could be detected, but the first group (G=0,14) grew much faster than the second (G=0,05).